Polymerization-induced thermal self-assembly (PITSA). Issue 2 (26th November 2014) - Figg, C. Adrian; Simula, Alexandre; Gebre, Kalkidan A.; Tucker, Bryan S.; Haddleton, David M.; Sumerlin, Brent S.
Abstract : Polymerization-induced thermal self-assembly (PITSA) was conducted using thermoresponsive poly( N -isopropylacrylamide) to result in micelle, worm, and vesicle polymeric morphologies. Abstract : Polymerization-induced self-assembly (PISA) is a versatile technique to achieve a wide range of polymeric nanoparticle morphologies. Most previous examples of self-assembled soft nanoparticle synthesis by PISA rely on a growing solvophobic polymer block that leads to changes in nanoparticle architecture during polymerization in a selective solvent. However, synthesis of block copolymers with a growing stimuli-responsive block to form various nanoparticle shapes has yet to be reported. This new concept using thermoresponsive polymers is termed polymerization-induced thermal self-assembly (PITSA). A reversible addition-fragmentation chain transfer (RAFT) polymerization of N -isopropylacrylamide from a hydrophilic chain transfer agent composed of N, N -dimethylacrylamide and acrylic acid was carried out in water above the known lower critical solution temperature (LCST) of poly( N -isopropylacrylamide) (PNIPAm). After reaching a certain chain length, the growing PNIPAm self-assembled, as induced by the LCST, into block copolymer aggregates within which dispersion polymerization continued. To characterize the nanoparticles at ambient temperatures without their dissolution, the particles were crosslinked immediately following polymerization at elevated temperatures via the reaction of the acid groups with a diamine in the presence of a carbodiimide. Size exclusion chromatography was used to evaluate the unimer molecular weight distributions and reaction kinetics. Dynamic light scattering and transmission electron microscopy provided insight into the size and morphologies of the nanoparticles. The resulting block copolymers formed polymeric nanoparticles with a range of morphologies ( e.g., micelles, worms, and vesicles), which were a function of the PNIPAm block length.